Effectiveness of Project Based Learning Model Based on Local Wisdom of Naposo Nauli Bulung - Dongoran, Indra Maulana; Hasibuan, Ahmad Safii; Harahap, Mei Adelina; Hadi, Anto J (Journal of Vocational and Career Education, 2023)
Current developments in science and technology not only have positive impacts but also negative impacts. This can be seen in the phenomenon of moral degradation that occurs in society involving school-age children, starting with the erosion of the sense of nationalism, the leadership of narcotics, alcoholism, and involvement in acts of violence. These various things pose a big threat to the future of the nation and the younger generation. In order to anticipate this, education has an important role because, through education the formation of national character with noble character can be realized. One method that can be used by teachers in the process of forming student character is implementing the Project Based Learning (PjBL) learning model in schools which contains values and character so this research is very important and urgent to be carried out immediately. Naposo Nauli Bulung local wisdom is local wisdom in the South Tapanuli area, North Sumatra which contains many good character values that are preserved by the people of South Tapanuli.This local wisdom is specifically for young people so they can work together to solve problems in society. For this reason, this research aims to analyze the influence of the Project Based Learning (PjBL) learning model based on local wisdom on the formation of student character at SMKN 4 Padang Sidempuan City.